ADVANCING UNDERSTANDING OF SERVICE-LEARNING: A CASE STUDY OF A UNIVERSITY IN MALAYSIA - Fong Wei Diong; Phaik Kin Cheah; Poh Chua Siah (Malaysian Journal of Learning and Instruction)
Purpose – This study aims to advance the understanding of service-learning within the context of Malaysian higher education, employing multiple qualitative approaches to source information relating to student perspectives whilst critically analysing findings through triangulation. The study explores how service-learning is conceptualized, experienced, and implemented from the viewpoints of university students through focus group interviews, complemented by a systematic examination of institutional documents related to service-learning programmes and policies, and observations of service-learning events.